A controllable exothermic composite basic solid formulation and its preparation process
Patent Information
- Application Number
- CN202610891344.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-20
AI Technical Summary
[0010]本发明主要目的在于提出一种可控放热复合碱性固体配方及其制备工艺,以解决上述现有技术存在的放热过程不可控、反应剧烈易产生安全隐患、反应产物悬浮难清理的技术问题,应用在发动机领域时,能够解决甲醇(氨燃料)缸内喷射雾化吸热导致的低温燃烧不稳定、失火风险高等问题
[0024]现有碱性自热材料一旦与水接触便会持续反应直至消耗完全,仅能通过添加缓凝剂调整整体反应速度,无法根据实际加热需求实时改变放热量。本发明制备的致密柱状固体结构,使水合反应仅发生在材料与水体的接触表面,通过调整材料浸入水体的深度即可改变有效接触面积,进而连续调节反应速率与放热量,能够实现反应的随时启停与平滑过渡,可匹配甲醇发动机的预热温度、预热时长需求,通过调控放热功率稳定加热循环水,保障极端环境下甲醇燃料预热效果,避免不必要的能源消耗。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of self-heating materials technology, and in particular to a controllable exothermic composite alkaline solid formulation and its preparation process. Background Technology
[0002] Methanol (ammonia fuel) engines typically employ in-cylinder injection. However, when methanol (ammonia fuel) is injected into the cylinder, it absorbs a significant amount of heat during atomization, leading to lower combustion chamber temperatures. This increases the required ignition energy, resulting in unstable combustion, poor performance, and even the risk of misfire, ultimately affecting the engine's effective performance and normal operation. In extreme low-temperature environments, the combined effect of fuel atomization heat absorption and ambient low temperature further exacerbates these problems. Low-temperature start-up preheating is a crucial step in ensuring the reliable operation of methanol (ammonia fuel) engines.
[0003] Currently, existing technologies disclose a scheme to preheat the engine using a heating boiler. However, this scheme requires fuel and batteries to continuously power the spark plugs to maintain ignition and combustion. The overall system structure is complex, and the cost of equipment installation and maintenance is high.
[0004] To eliminate dependence on external power sources and fuel, self-heating materials release heat through the reaction of chemical substances with water, achieving heating without external sources. They are convenient to use and not limited by the environment, and are gradually being applied to the preheating research of methanol (ammonia fuel) engines.
[0005] Currently, the most widely used self-heating materials on the market are calcium oxide-based and soda lime-based alkaline exothermic materials. These materials have widely available raw materials, low preparation costs, and high total heat release, which can meet most one-time rapid heating needs. However, in practical applications, existing alkaline exothermic materials still have many unresolved technical defects, which limit the further expansion of their application scope.
[0006] First, the exothermic process is uncontrollable, posing significant safety hazards. Existing alkaline exothermic materials are mostly in powder or loose briquettes, which undergo a rapid, large-area contact reaction upon contact with water. The exothermic rate is fast and cannot be adjusted, easily leading to localized sudden heating, boiling over, and splashing, posing a risk of burns. Furthermore, existing materials continue to react with water until completely consumed, making it impossible to adjust the heat release and heating rate in real time according to heating requirements. This not only wastes energy but also fails to meet the heating needs of different media and temperature scenarios, such as methanol (ammonia fuel) intake gradient preheating and engine whole-machine heating. Some technologies slow the reaction rate by adding retarders, but this only reduces the overall reaction speed and cannot achieve dynamic adjustment.
[0007] Secondly, the residue after the reaction is highly dispersible, making subsequent treatment difficult. Existing alkaline exothermic materials are prone to pulverization and disintegration during the reaction process, generating a large number of fine solid particles suspended in the reaction water, causing turbidity in the reaction system. This not only affects heating efficiency but also contaminates the reaction vessel, making cleaning difficult. Some technologies improve formability by adding organic binders, but binders reduce the total heat release of the material and cannot fundamentally solve the problem of reaction product suspension. Furthermore, binder decomposition at high temperatures may produce harmful substances.
[0008] Finally, precise stepless heat control cannot be achieved. Current technologies for heat release control often employ batch-addition of materials or separate packaging of the reaction, which is cumbersome and has low precision, allowing only coarse, level-based adjustments rather than continuous, smooth heat release regulation. No technology yet can achieve precise, stepless control of the heat release rate and calorific value through simple mechanical adjustments, such as changing the contact area between the material and water. This makes it unsuitable for applications requiring continuous and stable temperature control, such as the extreme preheating of methanol (ammonia fuel) engines.
[0009] The above background information is provided only to aid in understanding the inventive concept and technical solution of this invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above information was disclosed on the filing date of this patent application, the above background information should not be used to evaluate the novelty and inventiveness of this application. Summary of the Invention
[0010] The main objective of this invention is to propose a controllable exothermic composite alkaline solid formulation and its preparation process to solve the technical problems of uncontrollable exothermic processes, violent reactions that easily lead to safety hazards, and suspended reaction products that are difficult to clean in the prior art. When applied to the engine field, it can solve the problems of unstable low-temperature combustion and high risk of misfire caused by the endothermic atomization of methanol (ammonia fuel) in-cylinder injection. For example, by mixing alkaline substances with water to generate a large amount of heat, the heat can be used to heat the circulating water, achieving multiple preheating effects: preheating the engine coolant to warm up the engine in advance, preheating the engine oil to improve fluidity, and preheating the methanol (ammonia fuel) intake system to improve cold start ignition performance. Ultimately, it can achieve rapid engine preheating under extreme conditions, improve engine combustion performance and stability, and help the engine start quickly at low temperatures and reach operating conditions as soon as possible.
[0011] To achieve the above technical objectives, the present invention adopts the following technical solution:
[0012] A controllable exothermic composite alkaline solid formulation is composed of a main exothermic alkaline component, a coagulation-modifying component, and a reaction-stabilizing slow-release component. Each component is a dry solid powder, which is mixed and pressed into a dense columnar solid blank.
[0013] Preferably, the components are as follows by mass: 65-80 parts of the main exothermic alkaline component, 10-20 parts of the coagulation modification component, and 5-16 parts of the stable reaction slow-release component, and the total mass of the three components is 100 parts.
[0014] Preferably, the main exothermic alkaline component is a mixed powder of calcium oxide and sodium hydroxide, with a mass ratio of calcium oxide to sodium hydroxide of 4:1-6:1, a particle size of 80-120 mesh, a calcium oxide purity of ≥90%, and a sodium hydroxide purity of ≥96%.
[0015] Preferably, the coagulation modification component is a mixed powder of calcium silicate and bentonite, with a mass ratio of calcium silicate to bentonite of 2:1-3:1 and a particle size of 100-150 mesh.
[0016] Preferably, the stable reaction slow-release component is a porous inert alumina ceramic micro powder with a particle size of 100-150 mesh and an internal through-cell honeycomb microporous structure.
[0017] Preferably, the process includes, in sequence, a drying pretreatment step, a mixing and grinding step, a high-pressure static pressing molding step, and a curing and drying step.
[0018] Preferably, the drying pretreatment step is as follows: the main exothermic alkaline component, the coagulation modified component, and the stable reaction slow-release component are placed in a vacuum drying oven at 105-110℃ for 2-4 hours, and the moisture content of each component after drying is ≤0.5%.
[0019] Preferably, the mixing and grinding step is as follows: the dried three-component powder is added to a high-speed mixer according to the ratio, the mixing speed is 1200-1500 r / min, the mixing time is 15-25 min, and the particle size distribution deviation of the mixed powder is ≤±5%.
[0020] Preferably, the high-pressure static pressing step is as follows: the uniformly mixed powder is added into a columnar mold, the columnar mold is made of 304 stainless steel or lined with polytetrafluoroethylene coating, static pressing is performed with a pressure of 20-30MPa, the pressure holding time is 30-60s, and a columnar green blank is obtained after demolding.
[0021] Preferably, the curing and drying step is as follows: the columnar green body is placed in a forced-air drying oven at 80-90℃ for 6-11 hours, and the moisture content of the green body after drying is ≤0.2%; finally, a dense columnar solid green body is obtained.
[0022] The beneficial effects of this invention compared to the prior art include:
[0023] 1. Achieve dynamic stepless regulation of the heat release process.
[0024] Existing alkaline self-heating materials react continuously upon contact with water until completely consumed. The overall reaction rate can only be adjusted by adding retarders, but the heat release cannot be changed in real-time according to actual heating needs. The dense columnar solid structure prepared in this invention ensures that the hydration reaction occurs only at the contact surface between the material and water. By adjusting the depth of the material's immersion in water, the effective contact area can be changed, thereby continuously regulating the reaction rate and heat release. This allows for on-demand start-up and smooth transition of the reaction, matching the preheating temperature and duration requirements of methanol engines. By controlling the heat release power, the circulating water is stably heated, ensuring the preheating effect of methanol fuel under extreme environments and avoiding unnecessary energy consumption.
[0025] 2. Improve the stability and safety of the heat release process.
[0026] Existing powdered or loosely compressed alkaline exothermic materials undergo a large-area instantaneous contact reaction upon contact with water, easily leading to problems such as sudden localized temperature rises and water boiling and splashing, posing safety hazards. This invention introduces a stable, slow-release component into the formulation. This component is uniformly dispersed within the material and can adsorb and slowly release water, preventing instantaneous large-area contact between water and the alkaline exothermic component. This transforms concentrated, instantaneous heat release into continuous, uniform heat release, avoiding drastic fluctuations during the reaction process. This effectively improves the safety and stability of the heating effect during use, ensures uniform circulating water temperature, prevents localized overheating or insufficient preheating of methanol fuel, and further optimizes engine combustion.
[0027] 3. Solve the problem of suspended contamination of reaction products.
[0028] Existing alkaline exothermic materials are prone to pulverization and disintegration during the reaction process, generating a large number of fine solid particles suspended in the reaction water, causing turbidity in the reaction system. This not only reduces heat transfer efficiency but also contaminates the reaction vessel, making subsequent cleaning difficult. The coagulation-modifying component added in this invention interacts with the alkaline hydration products during the reaction, promoting the aggregation of reaction products into larger particles that settle rapidly. After the reaction, the water remains clear, reducing adhesion and contamination to the reaction vessel and significantly reducing the workload of subsequent cleaning.
[0029] 4. Enhance the stability of product storage and use.
[0030] Existing alkaline exothermic materials are mostly loose powders or low-density compressed briquettes with high porosity. During storage, they easily absorb moisture from the air, leading to premature reactions and product failure. This invention controls the moisture content of raw materials through a strict drying pretreatment process and uses a high-pressure static pressing process to prepare a dense solid structure, effectively isolating it from air and moisture intrusion and extending the product's shelf life. Simultaneously, the integrated solid structure facilitates handling and operation, eliminating the need to disassemble packaging or add materials in batches, simplifying the usage process.
[0031] 5. Simple structure and low cost, with good feasibility for large-scale production.
[0032] Compared to traditional boiler-type preheating solutions that rely on fuel combustion and continuous power supply, this invention eliminates the need for ignition, fuel supply, and continuous power supply systems, resulting in a simpler overall structure, lower equipment installation and maintenance costs, and independent operation even without external energy replenishment. The raw materials used in this invention are all commonly used industrial materials, widely available and inexpensive. The drying, mixing, and static pressing processes involved in the preparation are all mature industrial production technologies, requiring no special production equipment or complex operating procedures. By clearly defining the parameters of each process step, the structure and performance of different batches of products can be kept consistent, ensuring stable and controllable product quality, facilitating large-scale industrial production. Furthermore, no harmful substances are generated during the production process, meeting environmental protection requirements. Detailed Implementation
[0033] The present invention will be further described in detail below with reference to specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope and application of the present invention.
[0034] A controllable exothermic composite alkaline solid formulation is as follows:
[0035] I. Formula Composition and Raw Material Preparation
[0036] 1. The controllable exothermic composite alkaline solid formulation of the present invention consists of a main exothermic alkaline component, a coagulation modification component, and a reaction-stabilizing slow-release component. Each component is a dry solid powder, and the total mass fraction of the three components is 100 parts.
[0037] 2. By mass fraction, the main exothermic alkaline component is 65-80 parts, the coagulation modification component is 10-20 parts, and the reaction-stabilizing slow-release component is 5-16 parts.
[0038] 3. The main exothermic alkaline component is a mixed powder of calcium oxide and sodium hydroxide, with a mass ratio of calcium oxide to sodium hydroxide of 4:1-6:1, a particle size of 80-120 mesh, a calcium oxide purity of ≥90%, and a sodium hydroxide purity of ≥96%.
[0039] 4. The coagulation modification component is a mixed powder of calcium silicate and bentonite, with a mass ratio of calcium silicate to bentonite of 2:1-3:1 and a particle size of 100-150 mesh.
[0040] 5. The stable reaction slow-release component is a porous inert alumina ceramic micro powder with a particle size of 100-150 mesh and an internal through-cell honeycomb microporous structure.
[0041] II. Preparation Process Steps
[0042] 1. Drying pretreatment: Place the main exothermic alkaline component, the coagulation modified component, and the stable reaction slow-release component in a vacuum drying oven at 105-110℃ for 2-4 hours. After drying, the moisture content of each component is ≤0.5%.
[0043] 2. Mixing and grinding: Add the dried three-component powder to a high-speed mixer according to the ratio. The mixing speed is 1200-1500 r / min and the mixing time is 15-25 min. The particle size distribution deviation of the mixed powder is ≤±5%.
[0044] 3. High-pressure static pressing: The uniformly mixed powder is added into a columnar mold, which is made of 304 stainless steel or lined with polytetrafluoroethylene coating. Static pressing is performed under a pressure of 20-30MPa, and the holding time is 30-60s. After demolding, a columnar green body is obtained.
[0045] 4. Curing and drying: Place the columnar green body in a forced-air drying oven at 80-90℃ for 6-11 hours. After drying, the moisture content of the green body is ≤0.2%, and a dense columnar solid green body is finally obtained.
[0046] Technical principle of the invention:
[0047] 1. Overall Logic of Combinatorial Invention
[0048] This invention constructs a complete three-in-one technical system of "heat source supply - rate control - product processing" by compounding three types of solid powder raw materials with clearly defined functions and combining them with a high-pressure densification molding process. The three components are uniformly dispersed inside the dense preform, each undertaking an independent function, while cooperating with each other during the reaction process to achieve the comprehensive technical effects of controllable exothermic rate, stable reaction process, and less product suspension. This solves the technical problem that existing single or simple compound alkaline exothermic materials cannot simultaneously meet, and is suitable for the use requirements of methanol (ammonia fuel) engine preheating systems: relying on the hydration exothermic effect of alkaline materials to heat circulating water, and then using high-temperature circulating water to preheat the fuel intake air, thereby improving the low-temperature combustion problem caused by in-cylinder atomization endothermic heat absorption.
[0049] 2. The role of the main exothermic alkaline component
[0050] The main exothermic alkaline component consists of calcium oxide and sodium hydroxide mixed in a specified ratio. Calcium oxide undergoes a hydration reaction with water, releasing heat of hydration, which provides the main heat source for the system; sodium hydroxide dissolves in water, generating heat of solution, which supplements the system's heat. A 4:1 to 6:1 ratio of the two components balances the basic exothermic rate and the total exothermic capacity, avoiding the drawbacks of excessively rapid reaction rates with calcium oxide alone and low heat release per unit volume with sodium hydroxide alone. This component is the sole source of heat for the system; however, when used alone, its reaction with water is uncontrolled, easily leading to sudden heating. Furthermore, the generated hydroxide particles are small and easily suspended and dispersed in the water, failing to meet the requirements for constant-temperature heating of circulating water and stable preheating of methanol (ammonia fuel).
[0051] 3. The role of coagulation-modifying components
[0052] The coagulation-modifying component is composed of calcium silicate and bentonite in a specified ratio. In an alkaline aqueous environment, calcium silicate can undergo solid-phase fusion with the hydroxides generated during the hydration of the main exothermic component, promoting the adhesion of fine reaction products to form larger particles. Bentonite, relying on its layered structure, adsorbs free fine solid particles within the system. The combination of these two components enables rapid agglomeration and sedimentation of the reaction products. This component does not directly participate in the exothermic reaction; when added alone to the main exothermic component without rate control, a large amount of product is rapidly generated in a short time, and the modified component cannot complete adsorption and agglomeration in time, resulting in some particles remaining suspended.
[0053] 4. The role of the reaction-stabilizing and slow-release components
[0054] The stable reaction-release component is an inert alumina ceramic powder with a continuous honeycomb microporous structure. This component is chemically stable, insoluble in water, and does not participate in any exothermic reaction. Its internal micropores can adsorb moisture that has seeped into the green body and slowly diffuse it to the surface of the surrounding main exothermic component particles, prolonging the contact process between moisture and alkaline materials, thus transforming concentrated instantaneous exothermics into continuous and uniform exothermics. Using this component alone in combination with the main exothermic component only improves the stability of the exothermic reaction; it cannot solve the problem of reaction product suspension.
[0055] 5. Synergistic mechanism of the three components
[0056] The three components are interwoven within the dense green body, forming a sequential synergy during the reaction: moisture first contacts the surface of the green body, is adsorbed by the uniformly dispersed stable reaction-releasing components, and is slowly released, preventing the main exothermic component from experiencing rapid heating due to large-area contact with moisture in a short period of time; the main exothermic component undergoes a uniform hydration reaction under the action of the slowly released moisture, generating hydration products; the surrounding synchronously distributed agglomeration-modifying components immediately capture the newly formed fine product particles, promoting their aggregation and sedimentation. The absence of any one of these raw materials would prevent the simultaneous achievement of both stable and controllable exothermic reaction and minimal product suspension.
[0057] 6. Synergistic effect of dense molding structure and components
[0058] The dense, low-porosity preform prepared by high-pressure static pressing achieves deep synergy with the component functions. The dense structure restricts water penetration only from the outer surface of the preform inwards, ensuring a strict linear relationship between the immersion depth and the effective reaction area. This provides a structural basis for controlling the exothermic rate by adjusting the immersion depth. Simultaneously, the dense structure strengthens the spatial constraint between components, ensuring that the slow-release and condensation-modifying components can continuously act on the surrounding main exothermic components. This prevents component separation due to preform collapse during the reaction, maintains the stability of the synergistic effect, and enables continuously adjustable circulating water temperature, precisely matching the preheating requirements of methanol fuel under different low-temperature conditions.
[0059] To make the present invention more fully disclosed, more specific embodiments are described below.
[0060] Example 1:
[0061] A controllable exothermic composite alkaline solid formulation is as follows:
[0062] Formula composition:
[0063] The main exothermic alkaline component is 70 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 5:1, the particle size of the powder is 100 mesh, the purity of calcium oxide is 92%, and the purity of sodium hydroxide is 97%.
[0064] The coagulation modification component consists of 15 parts, in which the mass ratio of calcium silicate to bentonite is 2.5:1 and the powder particle size is 120 mesh.
[0065] The stable reaction slow-release component is 15 parts, which is a porous inert alumina ceramic micro powder with a particle size of 120 mesh and an internal through-hole honeycomb microporous structure.
[0066] Preparation process:
[0067] Drying pretreatment: Place the above three components in a vacuum drying oven at 108℃ for 3 hours. After drying, the moisture content of each component is ≤0.5%.
[0068] Mixing and grinding: Add the dried three-component powder to a high-speed mixer, mix at 1350 r / min for 20 min, and the particle size distribution deviation of the mixed powder is ≤ ±5%.
[0069] High-pressure static pressing: The uniformly mixed powder is added into a cylindrical mold made of 304 stainless steel, and static pressing is performed with a pressure of 25MPa for 45s. After demolding, a cylindrical green body is obtained.
[0070] Curing and drying: The columnar green body is placed in a forced-air drying oven at 85℃ and dried for 9 hours. After drying, the moisture content of the green body is ≤0.2%, and a dense columnar solid green body is finally obtained.
[0071] Example 2:
[0072] A controllable exothermic composite alkaline solid formulation is as follows:
[0073] Formula composition:
[0074] The main exothermic alkaline component is 65 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 4:1, the powder particle size is 80 mesh, the purity of calcium oxide is 90%, and the purity of sodium hydroxide is 96%.
[0075] The coagulation modification component consists of 20 parts, in which the mass ratio of calcium silicate to bentonite is 2:1, and the powder particle size is 100 mesh.
[0076] The stable reaction slow-release component is 15 parts, which is a porous inert alumina ceramic micro powder with a particle size of 100 mesh and an internal through-hole honeycomb microporous structure.
[0077] Preparation process:
[0078] Drying pretreatment: Place the above three components in a vacuum drying oven at 110℃ for 2 hours. After drying, the moisture content of each component is ≤0.5%.
[0079] Mixing and grinding: Add the dried three-component powder to a high-speed mixer, mix at 1200 r / min for 25 min, and the particle size distribution deviation of the mixed powder is ≤ ±5%.
[0080] High-pressure static pressing: The uniformly mixed powder is added into a columnar mold lined with polytetrafluoroethylene coating, and static pressing is performed with a pressure of 20MPa for 60s. After demolding, a columnar green body is obtained.
[0081] Curing and drying: The columnar green body is placed in a 90℃ forced-air drying oven and dried for 6 hours. After drying, the moisture content of the green body is ≤0.2%, and a dense columnar solid green body is finally obtained.
[0082] Example 3:
[0083] A controllable exothermic composite alkaline solid formulation is as follows:
[0084] Formula composition:
[0085] The main exothermic alkaline component is 75 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 5.5:1, the powder particle size is 110 mesh, the purity of calcium oxide is 93%, and the purity of sodium hydroxide is 98%.
[0086] The coagulation modification component consists of 12 parts, in which the mass ratio of calcium silicate to bentonite is 3:1 and the powder particle size is 130 mesh.
[0087] The stable reaction slow-release component consists of 13 parts, which is a porous inert alumina ceramic micro powder with a particle size of 130 mesh and an internal through-hole honeycomb microporous structure.
[0088] Preparation process:
[0089] Drying pretreatment: Place the above three components in a vacuum drying oven at 107℃ for 3 hours. After drying, the moisture content of each component is ≤0.5%.
[0090] Mixing and grinding: Add the dried three-component powder to a high-speed mixer, mix at 1380 r / min for 18 min, and the particle size distribution deviation of the mixed powder is ≤ ±5%.
[0091] High-pressure static pressing: The uniformly mixed powder is added into a cylindrical mold made of 304 stainless steel, and static pressing is performed with a pressure of 26MPa for 40s. After demolding, a cylindrical green body is obtained.
[0092] Curing and drying: The columnar green body is placed in a forced-air drying oven at 83℃ and dried for 9 hours. After drying, the moisture content of the green body is ≤0.2%, and a dense columnar solid green body is finally obtained.
[0093] Example 4:
[0094] A controllable exothermic composite alkaline solid formulation is as follows:
[0095] Formula composition:
[0096] The main exothermic alkaline component is 80 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 6:1, the powder particle size is 120 mesh, the purity of calcium oxide is 91%, and the purity of sodium hydroxide is 96%.
[0097] Ten parts of the coagulation modification component were used, in which the mass ratio of calcium silicate to bentonite was 2.5:1 and the particle size of the powder was 150 mesh.
[0098] Ten parts of the stable reaction slow-release component are porous inert alumina ceramic micro powders with a particle size of 150 mesh and an internal through-hole honeycomb microporous structure.
[0099] Preparation process:
[0100] Drying pretreatment: Place the above three components in a vacuum drying oven at 105℃ for 4 hours. After drying, the moisture content of each component is ≤0.5%.
[0101] Mixing and grinding: Add the dried three-component powder to a high-speed mixer, mix at 1500 r / min for 15 min, and the particle size distribution deviation of the mixed powder is ≤ ±5%.
[0102] High-pressure static pressing: The uniformly mixed powder is added into a columnar mold lined with polytetrafluoroethylene coating, and static pressing is performed with a pressure of 30MPa for 30s. After demolding, a columnar green body is obtained.
[0103] Curing and drying: The columnar green body is placed in a forced-air drying oven at 80℃ and dried for 11 hours. After drying, the moisture content of the green body is ≤0.2%, and a dense columnar solid green body is finally obtained.
[0104] Example 5:
[0105] A controllable exothermic composite alkaline solid formulation is as follows:
[0106] Formula composition:
[0107] The main exothermic alkaline component consists of 72 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 4.5:1, the powder particle size is 90 mesh, the purity of calcium oxide is 90%, and the purity of sodium hydroxide is 97%.
[0108] The coagulation modification component consists of 18 parts, in which the mass ratio of calcium silicate to bentonite is 2:1, and the powder particle size is 110 mesh.
[0109] Ten parts of the stable reaction slow-release component are porous inert alumina ceramic micro powders with a particle size of 110 mesh and an internal through-cell honeycomb microporous structure.
[0110] Preparation process:
[0111] Drying pretreatment: The above three components were placed in a vacuum drying oven at 109℃ for 2.5 hours. After drying, the moisture content of each component was ≤0.5%.
[0112] Mixing and grinding: Add the dried three-component powder to a high-speed mixer, mix at 1300 r / min for 22 min, and the particle size distribution deviation of the mixed powder is ≤ ±5%.
[0113] High-pressure static pressing: The uniformly mixed powder is added into a cylindrical mold made of 304 stainless steel and statically pressed at a pressure of 23MPa for 50s. After demolding, a cylindrical green body is obtained.
[0114] Curing and drying: The columnar green body is placed in a forced-air drying oven at 88℃ and dried for 7 hours. After drying, the moisture content of the green body is ≤0.2%, and a dense columnar solid green body is finally obtained.
[0115] Example 6:
[0116] A controllable exothermic composite alkaline solid formulation is as follows:
[0117] Formula composition:
[0118] The main exothermic alkaline component consists of 68 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 5:1, the powder particle size is 100 mesh, the purity of calcium oxide is 92%, and the purity of sodium hydroxide is 96%.
[0119] The coagulation modification component consists of 16 parts, in which the mass ratio of calcium silicate to bentonite is 3:1, and the powder particle size is 140 mesh.
[0120] The stable reaction slow-release component consists of 16 parts, which is a porous inert alumina ceramic micro powder with a particle size of 140 mesh and an internal through-hole honeycomb microporous structure.
[0121] Preparation process:
[0122] Drying pretreatment: The above three components were placed in a vacuum drying oven at 106℃ for 3.8 hours. After drying, the moisture content of each component was ≤0.5%.
[0123] Mixing and grinding: Add the dried three-component powder to a high-speed mixer, mix at 1400 r / min for 16 min, and the particle size distribution deviation of the mixed powder is ≤ ±5%.
[0124] High-pressure static pressing: The uniformly mixed powder is added into a columnar mold lined with polytetrafluoroethylene coating, and static pressing is performed with a pressure of 27MPa for 35s. After demolding, a columnar green body is obtained.
[0125] Curing and drying: The columnar green body is placed in a forced-air drying oven at 86℃ and dried for 8 hours. After drying, the moisture content of the green body is ≤0.2%, and a dense columnar solid green body is finally obtained.
[0126] Comparative Example 1:
[0127] Formula composition:
[0128] The main exothermic alkaline component is 75 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 3:1, the powder particle size is 110 mesh, the purity of calcium oxide is 93%, and the purity of sodium hydroxide is 98%.
[0129] The coagulation modification component consists of 12 parts, in which the mass ratio of calcium silicate to bentonite is 3:1 and the powder particle size is 130 mesh.
[0130] The stable reaction slow-release component consists of 13 parts, which is a porous inert alumina ceramic micro powder with a particle size of 130 mesh and an internal through-hole honeycomb microporous structure.
[0131] Preparation process:
[0132] Completely consistent with Example 3.
[0133] Comparative Example 2:
[0134] Formula composition:
[0135] The main exothermic alkaline component is 75 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 5.5:1, the powder particle size is 110 mesh, the purity of calcium oxide is 93%, and the purity of sodium hydroxide is 98%.
[0136] No coagulation-modifying components are added.
[0137] The stable reaction slow-release component consists of 13 parts, which is a porous inert alumina ceramic micro powder with a particle size of 130 mesh and an internal through-hole honeycomb microporous structure.
[0138] Preparation process:
[0139] Completely consistent with Example 3.
[0140] Comparative Example 3:
[0141] Formula composition:
[0142] The main exothermic alkaline component is 75 parts, in which the mass ratio of calcium oxide to sodium hydroxide is 5.5:1, the powder particle size is 110 mesh, the purity of calcium oxide is 93%, and the purity of sodium hydroxide is 98%.
[0143] The coagulation modification component consists of 12 parts, in which the mass ratio of calcium silicate to bentonite is 3:1 and the powder particle size is 130 mesh.
[0144] No stable reaction-sustaining components are added.
[0145] Preparation process:
[0146] Completely consistent with Example 3.
[0147] Comparative Example 4:
[0148] Formula composition:
[0149] Completely consistent with Example 3.
[0150] Preparation process:
[0151] Drying pretreatment: The above three components were placed in a vacuum drying oven at 100℃ for 3.5 hours. After drying, the moisture content of each component was 0.8%.
[0152] The remaining mixing and grinding, high-pressure static pressing molding, curing and drying steps are completely consistent with those in Example 3.
[0153] Comparative Example 5:
[0154] Formula composition:
[0155] Completely consistent with Example 3.
[0156] Preparation process:
[0157] High-pressure static pressing: The uniformly mixed powder is added into a cylindrical mold made of 304 stainless steel, and static pressing is performed with a pressure of 15MPa for 40s. After demolding, a cylindrical green body is obtained.
[0158] The remaining drying pretreatment, mixing and grinding, curing and drying steps are completely consistent with those in Example 3.
[0159] Comparative Example 6:
[0160] Formula composition:
[0161] Completely consistent with Example 3.
[0162] Preparation process:
[0163] Curing and drying: The columnar green body was placed in a forced-air drying oven at 83℃ and dried for 4 hours. The moisture content of the green body after drying was 0.5%.
[0164] The remaining drying pretreatment, mixing and grinding, and high-pressure static pressing steps are completely consistent with those in Example 3.
[0165] Single-factor experiment:
[0166] This section conducts single-factor experiments on five core preparation process parameters. All experiments keep other process conditions and formulation composition fixed (using the formulation of Example 3), and only change a single target parameter to verify the rationality and optimal value of the parameter range.
[0167] 1. Single-factor experiment on drying pretreatment temperature
[0168] Fixed conditions: drying time 3h, mixing speed 1380r / min, molding pressure 26MPa, curing and drying time 9h. The results are shown in Table 1.
[0169] Experimental parameter range: 105℃, 106℃, 107℃, 108℃, 109℃, 110℃.
[0170]
[0171] Conclusion and Analysis: When the drying temperature is below 107℃, the adsorbed water inside the raw material is not completely removed, resulting in a high moisture content. After pressing and molding, tiny pores remain inside the green body, leading to a decrease in density. Moisture easily penetrates the interior along these pores, disrupting the linear relationship between penetration depth and contact area, and reducing the linearity of heat control. When the drying temperature is above 107℃, slight thermal decomposition occurs on the surface of the sodium hydroxide powder, leading to a decrease in powder activity. This results in a decrease in the density of the green body after pressing and molding, also affecting the linearity of heat control. The optimal drying pretreatment temperature in this experiment is 107℃.
[0172] 2. Single-factor experiment on drying pretreatment time
[0173] Fixed conditions: drying temperature 107℃, mixing speed 1380r / min, molding pressure 26MPa, curing and drying time 9h.
[0174] Experimental parameter range: 2h, 2.5h, 3h, 3.5h, 4h. The results are shown in Table 2.
[0175]
[0176] Conclusion and Analysis: When the drying time is less than 3 hours, the moisture content of the raw material gradually decreases with increasing drying time, the density of the green body gradually increases, the risk of moisture absorption failure during storage decreases, and the storage stability gradually improves. When the drying time exceeds 3 hours, the moisture content of the raw material has already dropped to a low level, and further extending the drying time has limited effect on reducing the moisture content. Moreover, prolonged high-temperature drying can lead to slight agglomeration of powder particles on the surface, affecting the uniformity of pressing and molding, and slightly decreasing the density and storage stability of the green body. The optimal drying pretreatment time in this experiment is 3 hours.
[0177] 3. Single-factor experiment on mixing and grinding speed
[0178] Fixed conditions: drying temperature 107℃, drying time 3h, molding pressure 26MPa, curing and drying time 9h.
[0179] Experimental parameter ranges: 1200 r / min, 1260 r / min, 1320 r / min, 1380 r / min, 1440 r / min, 1500 r / min. The results are shown in Table 3.
[0180]
[0181] Conclusion and Analysis: When the mixing speed is below 1380 r / min, the uniformity of the three-component powder mixing gradually increases with increasing speed. The stable reaction slow-release component and the agglomeration modification component are more evenly distributed in the main exothermic matrix, the fluctuation of the exothermic process is reduced, and the product sedimentation rate is improved. When the mixing speed is above 1380 r / min, the powder particles exhibit over-grinding, the microporous structure of some alumina micropowder is destroyed, the slow-release effect decreases, resulting in a slight increase in exothermic temperature fluctuation, an increase in ultrafine particles, and a slight decrease in product sedimentation rate. The optimal mixing and grinding speed in this experiment is 1380 r / min.
[0182] 4. Single-factor experiment on high-pressure static pressing pressure
[0183] Fixed conditions: drying temperature 107℃, drying time 3h, mixing speed 1380r / min, curing and drying time 9h.
[0184] Experimental parameter range: 20MPa, 22MPa, 24MPa, 26MPa, 28MPa, 30MPa. The results are shown in Table 4.
[0185]
[0186] Conclusion and Analysis: When the molding pressure is below 26 MPa, the porosity of the preform gradually decreases with increasing pressure, the density of the preform increases, and moisture can only react from the surface. The linear relationship between penetration depth and contact area is more accurate, and the linearity of heat control is improved. At the same time, the internal voids of the preform decrease, the proportion of effective exothermic components increases, and the total heat release increases. When the molding pressure is above 26 MPa, the porosity of the preform further decreases, but excessive compaction makes it difficult for moisture to penetrate into the surface of the preform, slows down the reaction rate, and prevents some internal alkaline components from fully participating in the reaction. The total heat release decreases slightly, and the linearity of heat control also decreases slightly. The optimal high-pressure static molding pressure in this experiment is 26 MPa.
[0187] 5. Single-factor experiment on curing and drying time
[0188] Fixed conditions: drying temperature 107℃, drying time 3h, mixing speed 1380r / min, molding pressure 26MPa.
[0189] Experimental parameter range: 6h, 7h, 8h, 9h, 10h, 11h, and the results are shown in Table 5.
[0190]
[0191] Conclusion and Analysis: When the curing time is less than 9 hours, the residual moisture inside the green body is gradually removed with the extension of curing time, the internal stress of the green body is released, the radial density deviation decreases, the reaction rate of each part is more consistent, and the exothermic stability is improved. When the curing time is more than 9 hours, the moisture content of the green body has dropped to a low level. Further extending the curing time will lead to slight dry cracking on the surface of the green body, a slight increase in radial density deviation, and a slight decrease in exothermic stability. The optimal curing and drying time in this experiment is 9 hours.
[0192] Product performance index testing:
[0193] 1. Testing Items and Methods
[0194] Total heat release: Measured using an oxygen bomb calorimeter, unit: kJ / kg.
[0195] Exothermic temperature fluctuation: The water temperature is monitored in real time using thermocouples, and the difference between the highest and lowest temperatures during the reaction process is calculated in °C.
[0196] Product sedimentation rate: After the reaction is completed, let it stand for 30 minutes, take the supernatant, filter and dry it, and calculate the percentage of suspended residue mass to total product mass. Sedimentation rate = 1 - suspended residue mass / total product mass × 100%.
[0197] Storage stability: The number of days the sample is stored in an environment with a temperature of 25°C and a relative humidity of 60% until the heat release of the sample decreases to 90% of the initial value.
[0198] Thermal linearity: The exothermic power was measured at immersion depths of 20%, 40%, 60%, 80%, and 100%, and the linear correlation coefficient R between the exothermic power and the immersion depth was calculated. 2 .
[0199] 2. Test Results and Analysis
[0200] All samples were tested under the same conditions, and the results are shown in Table 6:
[0201]
[0202] Data comparison and theoretical analysis:
[0203] All samples were tested under the same conditions, and the results are shown in the table above. The overall performance of the example group was better than that of the comparative group. The average total heat release of the example group was 1346.1 kJ / kg, the average heat release temperature fluctuation was 2.7℃, the average product sedimentation rate was 95.9%, the average storage stability was 259 days, and the average thermal control linearity was 0.980. All indicators were at a high level.
[0204] 1. Comparative Example 1 altered the mass ratio of calcium oxide to sodium hydroxide in the main exothermic alkaline component, exceeding the 4:1-6:1 range specified in this invention. This resulted in a decrease in the total exothermic heat to 1297.2 kJ / kg, an increase in the exothermic temperature fluctuation to 4.8℃, and varying degrees of decrease in other indicators. This demonstrates that the ratio of calcium oxide to sodium hydroxide is a necessary condition for ensuring the basic exothermic performance of the system; deviation from this range leads to a simultaneous decrease in both exothermic capacity and stability.
[0205] 2. Comparative Example 2 did not add any coagulation-modifying components, and all other conditions were completely consistent with Example 3. Its product sedimentation rate decreased to 68.1%, while the total heat release, heat release temperature fluctuation, storage stability, and thermal control linearity were similar to those of Example 3. This directly proves that the coagulation-modifying components are the core technical feature for achieving rapid agglomeration and sedimentation of reaction products. Their absence will lead to turbidity of the water after the reaction, increasing the difficulty of subsequent cleaning.
[0206] 3. Comparative Example 3 did not add the stable reaction-controlled release component, and all other conditions were completely consistent with Example 3. Its exothermic temperature fluctuation increased to 7.9℃, while other indicators were close to those of Example 3. This directly proves that the stable reaction-controlled release component is the core technical feature for achieving stable exothermic reaction, and its absence will lead to a violent reaction process and pose safety hazards.
[0207] 4. Comparative Example 4 reduced the drying pretreatment temperature, resulting in a higher moisture content in the raw materials. Consequently, the final product's storage stability decreased to 166 days, and other indicators also declined to some extent. This demonstrates that the drying pretreatment temperature range defined in this invention is a necessary condition for ensuring product storage stability. Insufficient temperature leads to excessive residual moisture in the raw materials, making them prone to premature reaction and failure during storage.
[0208] 5. Comparative Example 5 reduced the high-pressure static pressing, resulting in higher porosity of the green body, a decrease in thermal control linearity to 0.935, and a certain degree of decline in other indicators. This indicates that the molding pressure range defined in this invention is a necessary condition to ensure thermal control linearity. Insufficient pressure will lead to insufficient green body density, making it easier for moisture to penetrate along the internal pores and disrupting the linear relationship between penetration depth and reaction area.
[0209] 6. Comparative Example 6 shortened the curing and drying time, resulting in higher residual moisture content in the green body, a decrease in storage stability to 193 days, and a certain degree of decline in other indicators. This indicates that the curing and drying time range defined in this invention is a necessary condition to ensure the final performance of the product. Insufficient time will lead to incomplete release of internal stress in the green body, and residual moisture will affect storage stability.
[0210] This invention, through the rational selection and limitation of formulation components and preparation process parameters, constructs a three-in-one technical system of "heat source supply - rate control - product processing," achieving comprehensive technical effects such as controllable exothermic rate, stable reaction process, and easy product cleanup. All performance indicators are superior to comparative examples that modify a single technical feature, proving that the technical solution of this invention is an improvement over existing technologies.
[0211] The above description, in conjunction with preferred embodiments, provides a further detailed explanation of the present invention and should not be construed as limiting the specific implementation of the invention to these descriptions. For those skilled in the art, various substitutions or modifications can be made to these described embodiments without departing from the inventive concept, and all such substitutions or modifications should be considered within the scope of protection of the present invention.
[0212] Although the invention and its advantages have been described in detail, it should be understood that various changes, substitutions, and modifications can be made without departing from the spirit and scope of the invention. Furthermore, the scope of the invention is not limited to the specific embodiments of the processes, methods, and steps described in the specification. From the disclosure of this invention, those skilled in the art will readily utilize existing or future processes, methods, steps that substantially perform the same function or achieve the same results as the corresponding embodiments described herein. Therefore, the appended claims are intended to cover such processes, methods, steps.
Claims
1. A controllable exothermic composite alkaline solid formulation, characterized in that, It consists of a main exothermic alkaline component, a coagulation-modifying component, and a reaction-stabilizing slow-release component. Each component is a dry solid powder, which is mixed and pressed into a dense columnar solid blank.
2. The controllable exothermic composite alkaline solid formulation according to claim 1, characterized in that, The components, by mass fraction, are as follows: 65-80 parts of the main exothermic alkaline component, 10-20 parts of the coagulation-modifying component, and 5-16 parts of the stable reaction-releasing component, with the total mass fraction of the three components being 100 parts.
3. The controllable exothermic composite alkaline solid formulation according to claim 2, characterized in that, The main exothermic alkaline component is a mixed powder of calcium oxide and sodium hydroxide, with a mass ratio of calcium oxide to sodium hydroxide of 4:1-6:1, a particle size of 80-120 mesh, a calcium oxide purity of ≥90%, and a sodium hydroxide purity of ≥96%.
4. The controllable exothermic composite alkaline solid formulation according to claim 2, characterized in that, The coagulation modification component is a mixed powder of calcium silicate and bentonite, with a mass ratio of calcium silicate to bentonite of 2:1-3:1 and a particle size of 100-150 mesh.
5. The controllable exothermic composite alkaline solid formulation according to claim 2, characterized in that, The stable reaction slow-release component is a porous inert alumina ceramic micro powder with a particle size of 100-150 mesh and an internal through-cell honeycomb microporous structure.
6. The preparation process of the controllable exothermic composite alkaline solid formulation according to claim 1, characterized in that, The process includes, in sequence, a drying pretreatment step, a mixing and grinding step, a high-pressure static pressing molding step, and a curing and drying step.
7. The preparation process of the controllable exothermic composite alkaline solid formulation according to claim 6, characterized in that, The drying pretreatment step is as follows: the main exothermic alkaline component, the coagulation modified component, and the stable reaction slow-release component are placed in a vacuum drying oven at 105-110℃ for 2-4 hours. After drying, the moisture content of each component is ≤0.5%.
8. The preparation process of the controllable exothermic composite alkaline solid formulation according to claim 6, characterized in that, The mixing and grinding step is as follows: the dried three-component powder is added to a high-speed mixer according to the ratio, the mixing speed is 1200-1500 r / min, the mixing time is 15-25 min, and the particle size distribution deviation of the mixed powder is ≤±5%.
9. The preparation process of the controllable exothermic composite alkaline solid formulation according to claim 6, characterized in that, The high-pressure static pressing molding step is as follows: the uniformly mixed powder is added into a columnar mold, which is made of 304 stainless steel or lined with polytetrafluoroethylene coating. Static pressing molding is performed with a pressure of 20-30MPa and a holding time of 30-60s. After demolding, a columnar green body is obtained.
10. The preparation process of the controllable exothermic composite alkaline solid formulation according to claim 6, characterized in that, The curing and drying steps are as follows: the columnar green body is placed in a forced-air drying oven at 80-90℃ for 6-11 hours, and the moisture content of the green body after drying is ≤0.2%; finally, a dense columnar solid green body is obtained.